Review of “Doing Poetic Inquiry” by Helen Owton (2017) - MacKenzie-Dawson, Sarah K. (Art/Research International)

(untitled) (University of Alberta, 2022)
Directed toward the novice, Helen Owton’s (2017) book, Doing Poetic Inquiry, introduces the reader to poetry as an approach to research that allows one to enter into a phenomenological space of relational experience and understanding. Striving toward accessibility, she captures the tensions that exists within qualitative research by offering a guide that is both personal and methodologically orientated. Across the space of this review, I blend found poetry with prose as a means of entering into dialogue with this work. This dialogue lives in a messy space of intention and understanding where knowing lives within the body—the heart, the personal and political. Owton’s work is a compassionate gesture that offers concrete examples and suggestions inviting the reader to reconsider their own research practices and the discursive spaces in which those practices live.